963. Non-Invasive Detection of Cardiovascular Risk in People Living with HIV in Miami. (31st December 2020) - Salguero, Douglas; Galo, Jason; Rodriguez, Jornan; Pester, Mollie; Chedebau, Alejandro; Lang, Barbara; Parker, Meela; Gonzales, Alex; Alcaide, Maria L; Hurwitz, Barry; Schneiderman, Neil; Martinez, Claudia
Abstract: Background: HIV is a risk factor for Cardiovascular Disease (CVD), and CVD is the leading cause of mortality among Hispanics (H). Hispanics in the US are disproportionately affected by HIV with higher rates of HIV related morbidity and mortality, as well as adverse CVD outcomes. This study sought to identify early markers of CVD risk among Hispanics living with HIV. Methods: Interim analysis of 38 H and non-Hispanics (NH) people living with HIV (PLWH), stable on antiretroviral regimen, 30-50 years of age, without previously detected CVD. Demographics, CD4 T cells, HIV RNA viral load, traditional early markers of CVD risk were collected. CVD risk markers were obtained with non-invasive tools: epicardial adipose tissue (EAT) thickness was assessed by echocardiogram; arterial stiffness was assessed by applanation tonometry sequentially at the carotid, femoral and radial arteries (including central augmentation index - AI, peripheral AI, radial pulse wave velocity - PWV, and femoral PWV). The Framingham Coronary Event Risk Score (FCER) was calculated for each subject. Descriptive and linear regression analysis for predictors of FCER measures were age adjusted. Results: Among the 38 participants enrolled the mean age was 42 years, 80% male, H 76%, NH 24%, Black 16%, with mean BMI of 26.7. 45% met clinical criteria for metabolic syndrome: high waist girth 24%, high blood pressure 18%, high Fasting Glucose 16%, high total cholesterol 21%, high triglycerides 26%, low HDL 45%, high LDL 18%, high TC/HDL ratio 68%. The mean EAT was 3.8 mm, mean central AI 20.2 %, mean peripheral AI 73%, mean femoral PWV 28.8 m/s, mean radial PWV 8.7 m/s. Older age was associated with greater central AI (r = 0.37, p =.01) and peripheral AI (r = 0.38, p =.01) but not with increased EAT. Regression analysis predicting FCER relationships showed radial PWV as an independent predictor of increased FCER (r = 0.36, p < .05). Conclusion: Risk factors leading to CVD are common among this group of PLWH and radial PWV is a moderate predictor of increased FCER. Although measures of arterial stiffness are available, they are not routinely used to assess CVD risk. Further studies should evaluate the use of noninvasive methods for diverse PLWH, to prevent the development of CVD. Disclosures: All Authors : No reported disclosures